Other Backward Classes and the politics of reservations in India: Past and present - Zoya Hasan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
The paper examines the existing state of reservations, more specifically, reservation policies and reservations for government jobs for the Other Backward Classes (OBCs) in India. It discusses the progression and ramifications of these policies and how they have affected the democratization of politics. However, reservations for the OBCs were controversial, unlike the reservations for the Scheduled Castes and Scheduled Tribes, which were an accepted feature of government policy since Independence. Most of the disputes relate to the classification of beneficiaries in terms of social and economic discrimination with regard to caste and class and the exclusion of the creamy layer, or the well-off, among them. Controversies apart, OBC reservations have changed the social composition of educational institutions, bureaucracy, and legislatures and local government; as a consequence, these institutions are no longer the monopoly of the upper castes. These changes have occurred in the past few decades and are largely attributable to the unprecedented regime of reservations India adopted at the time of Independence, which was expanded further in subsequent decades. This analysis is situated at the intersection of public policy and political processes since reservations in India are linked to the project of inclusion of underrepresented groups in public institutions, which may otherwise be excluded by default. The strongest rationale for inclusion of particular social groups lies in the manner in which public institutions work-which is to say they often do not provide adequate policy concern for groups that are marginalized and deprived. It is this exclusion that provides the strongest justification for India's reservation regime.
Keywords: 330; reservations; reservation policy; government jobs; creamy layer; caste; class; caste inclusion